Co-designing with senior citizens: Methodology and evaluation of Project Cordon Gris - Rodrigues, B.; Gerardo, F. (II Cogreso Internacional Envejecimiento Activo, Calidad de vida y Género, 2017)
Background and objectives: Project Cordon Gris (AAL) aims to improve the quality of life of senior citizens using new technologies to prevent malnutrition among this population. The project is developing a prototype for a data-driven inclusive service that provides online grocery shopping assistance, health track and meal recommendations according to user’s profile and preferences. This presentation is intended to discuss the implementation of the project in the Portuguese context. Research design and methods: Since its inception in May 2017, project CordonGris is actively engaging elderly people in different development stages of the prototype: research, design and test. Such participation included several activities: questionnaires, aiming at understanding seniors’ life habits, independence and nutritional assessment; focus groups, to define the type of technology and service to be provided to the target group; intermediate tests, to collect data on the acceptability and usability of the prototype. Field trials will involve a sample of 120 participants aged over 65. 12 professionals from different social service establishments are being involved in the design of the field trials and will continue to provide support during its execution. Discussion and implications: The methodology described above aims to promote active ageing; social participation and social learning among Portuguese seniors, in addition to the general goals of the project. Therefore, evaluation of the field trials will entail (i) pre-test and post-test questionnaires, (ii) ongoing evaluation by means of weekly meetings with participants and professional caregivers plus (iii) focus groups at the end of each pilot trial phase. Between each field trial phase, feedback collected from participants will lead to prototype changes, thereby promoting an effective methodology of co-design.